BODY FAT DISTRIBUTION AND CARDIO-METABOLIC RISK FACTORS IN MIXED-ANCESTRY SOUTH AFRICAN WOMEN AND MEN. (June 2018) - Kengne, A.P.; Davidson, F.E.; Matsha, T.E.; Erasmus, R.T.; Goedecke, J.E.
Abstract : Objective: Obesity is a well-known risk factor for CVD and metabolic diseases, but body fat distribution appears to be a more significant discriminator of risk than generalized adiposity. We investigated the relationship between body fat distribution and cardio-metabolic risk in mixed-ancestry South African (SA) men and women, and explore the effect of menopausal status on these relationships in women. Design and method: In a cross-sectional study, 207 mixed-ancestry SA women and 46 men underwent measures of body composition using dual-energy X-ray absorptiometry (DXA), blood pressure, oral glucose tolerance, lipid profile and high sensitivity C-reactive protein (hs-CRP). Robust regression analyses were used to investigate the associations between body fat distribution and cardio-metabolic risk factors (insulin resistance, lipid levels, blood pressure and inflammatory markers), adjusting for age and sex. In addition, we explored the interactions between sex and body composition on cardio metabolic risk factors, adjusting for age, and in women, between menopausal age and body composition. Results: Men had less percentage fat mass (%FM, 26.5 (19.9–32.5)% vs. 44.0 (39.8–48.6)%, p < 0.001), but more central (p < 0.001) and less peripheral fat (p < 0.001) than the women. Post-menopausal women had greater %FM (p < 0.001), waist and visceral adipose tissue (VAT) (both p < 0.004), and less gynoid %FM (p = 0.001) than pre-menopausal women. After adjusting for age and sex, VAT accounted for greatest variance in insulin resistance (HOMA-IR, R2 = 0.19), while trunk %FM and leg %FM accounted for greatest variance in triglyceride (R2 = 0.13) and high-density lipoprotein cholesterol concentrations (HDL-C) (R2 = 0.14), respectively. The association between fat mass and regional subcutaneous adipose tissue (SAT) and cardiometabolic risk factors differed by sex and menopausal status. Conclusions: VAT was the most significant correlate of cardiometabolic risk in mixed ancestry men and women, irrespective of sex and menopausal status